What kind of America will Gen Xers inherit? - Kotkin, Joel; Friedman, David (American Enterprise)
Conventional wisdom holds that the U.S. is entering an era of sustained prosperity, but underlying this optimism is the baby-boom generation's ability to misperceive the world around them. Their faith in a “new era economy” ignores the real threats to prosperity that Generation X leaders will have to address. The real challenge for these leaders will be separating the hype from the reality. Details are provided of five boomer-generated myths for Generation X to watch out for: that the soaring stock market of the 1990s signals the dawn of broad and sustained prosperity; that the U.S. has an insurmountable technological lead that guarantees future prosperity; that after decades of decay, U.S. cities are enjoying a remarkable revival; that the U.S.'s social problems will be solved by prosperity; and that democratic capitalism has triumphed across the globe.